A study on promoting the intensive use of industrial land in China through governance: A game theoretical approach - Jiaojiao Luo; Yuzhe Wu; Charles L. Choguill; Xiaobin Zhang (Journal of Urban Management, 2022)
Extensive use of industrial land has been typical for many cities in China since the end of the previous century. One of the most important reasons is the local governments' strategy choice in land use. In this research, a governance structure from the view of the tax-sharing system and the performance appraisal system is constructed to explain the causes of extensive land use using game theory analysis. The key finding is that the governance structure in industrial land use is an organizational structure composed of the central government, local government and the market, and these three participants hold inter-conditioned relationships so as to form a closed loop. However, a bottom-up relationship chain from the market is absent in this structure, which makes it difficult to rely on local governments to implement intensive use of industrial land by themselves. Game equilibrium analysis shows that if a performance penalty coefficient is considered to refine the existing performance appraisal system to help produce a market feedback, the possibility of local governments adopting extensive land use strategies will be reduced.
Keywords: 710; Game theory; Governance structure; Industrial land; Intensive use; Urban growth